2009
DOI: 10.1159/000206491
|View full text |Cite
|
Sign up to set email alerts
|

How Much Residual Hearing Is ‘Useful’ for Music Perception with Cochlear Implants?

Abstract: Aim: To compare performance on a song recognition task of bilaterally combined electric and acoustic hearing (bimodal stimulation) with electric or acoustic hearing alone. Methods:Subjects were 14 adults with cochlear implants (CI) who continued to use a hearing aid (HA) in one/both ears. Subjects were asked to identify excerpts from 15 popular songs, which were familiar to them, presented in a random order via a single loudspeaker. Presentation conditions were fixed in order: bimodal, CI alone and then HA alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 31 publications
7
53
0
1
Order By: Relevance
“…This is in agreement with other studies showing that CI listeners perceive rhythmic information much better than musical pitch, and that there are no differences between CI-only and CI+HA listeners in conditions of musical rhythm (Dorman et al, 2008;Drennan & Rubinstein, 2008;El Fata et al, 2009;Gfeller et al, 2012;Kong et al, 2005;.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with other studies showing that CI listeners perceive rhythmic information much better than musical pitch, and that there are no differences between CI-only and CI+HA listeners in conditions of musical rhythm (Dorman et al, 2008;Drennan & Rubinstein, 2008;El Fata et al, 2009;Gfeller et al, 2012;Kong et al, 2005;.…”
Section: Discussionsupporting
confidence: 93%
“…Dorman et al (2008) MUSIC PERCEPTION WITH HEARING AIDS 4 showed that in addition to improvements in speech perception, CI recipients who also relied on an HA in everyday use were more accurate in identifying melodies using both their CI and HA than when listening with only their CI. Two additional studies have reported better melody recognition when listeners use CIs and HAs as compared to CIs alone (El Fata, James, Laborde, & Fraysse, 2009;Kong, Stickney, & Zeng, 2005). These studies assume that the benefit of the low frequency hearing from the HA on music recognition is pitch perception.…”
mentioning
confidence: 99%
“…As for listeners with normal hearing and BiCI users, the combined use of a CI and contralateral HA increases overall loudness (Blamey et al, 2000b;Potts et al, 2009). Several studies have shown benefit of adding a contralateral HA to a CI in regards to melody recognition (Kong et al, 2005;Dorman et al, 2008;El Fata et al, 2009). The finding that results for the HA alone are usually as good as the bimodal condition suggests performance is predominantly mediated by the low-frequency information available in the HA signal.…”
Section: Psychophysical Outcomes With Bici and Bimodal Listenersmentioning
confidence: 99%
“…Most of the authors agreed that, provided there was enough residual acoustic hearing, a contralateral HA increased the quality of hearing in the majority of users. This was particularly the case under special listening conditions such as directional hearing and hearing in background noise [Ching et al, 2004;Mok et al, 2006;Novak et al, 2007] as well as when listening to music [Gfeller et al, 2006;El Fata et al, 2009]. Further inconsistencies in outcomes of the combined bimodal mode may be related to the fact that only after adequate adjustment of HA and CI, a positive effect could be detected [Ching et al, 2001].…”
Section: Eas Versus Bimodal Eas Plus Contralateral Ha and Bilateral Easmentioning
confidence: 99%